About the translation of complex lexical units: challenges involving locutions, collocations and phraseological statements - Garcia Simao, Angelica Karim [UNESP] (Univ Federal Parana, Editora, 2016)
The aim of this paper is to analyze the translation of phraseological units from Spanish into Portuguese. Phraseological units are defined as lexical units constituted of two graphic words at the lower level and compound sentences at the upper level. We focus on the concrete procedures which are visible in the result of the translated text and which reveal the techniques by means of the analysis of the equivalent units proposed. Results show differences regarding translation techniques related to locutions, collocations and phraseological statements and allow the conclusion that different methods may be used in the translation of locutions and phraseological statements without compromising expressive and stylistic elements of the literary text. Particularly in the case of collocations, our data suggests the need of greater attention to the decoding of these units by the translator.
Keywords: lexicology; phraseology; translation